Effect of spinning conditions on the fabrication of cellulose acetate hollow fiber membrane for CO2 separation from N2 and CH4 - Mubashir, M. (2019)
In the current work, effect of spinning conditions including, take-up speed and air-gap distance and post-treatment methods on the fabrication of cellulose acetate hollow fiber membranes (CA-HFMs) for CO2/N2 and CO2/CH4 separations have been reported. The gas permeation results obtained in this work revealed that permeances of gases were decreased with increase in take-up speed from free fall to 12.2 m/min. Meanwhile, gas pair selectivities increased with increasing take-up speed. Subsequently, increment in air-gap distance produced the âVâ pattern for gases permeances and âAâ pattern of gas pair selectivities for all CA-HFMs spun at different take-up speeds. Therefore, optimum take-up speed and air gap distance of CA-HFMs of 12.2 m/min and 5.0 cm were obtained, respectively. CA-HFM spun at optimum spinning conditions showed the highest CO2/CH4 and CO2/N2 ideal selectivities of 7.9 and 6.0, respectively. On the other hand, permeation results also demonstrated that the CO2/CH4 and CO2/N2 ideal selectivities of PDMS coated CA-HFMs were higher about 70.9 and 84.1, respectively, compared to those values obtained from thermally treated CA-HFMs. Therefore, PDMS coating is considered as an effective approach to seal the macro-voids of HFMs compared to the thermal treatment in order to achieve higher permeation performance for CO2 separations. In addition, permeation results also manifested that the CA-HFM fabricated at optimum conditions has incredible worth from the prospective of industrial separations of CO2 from flue and natural gas. Â© 2018 Elsevier Ltd